A Novel Cervical Sagittal Classification for Asymptomatic Population Based on Cluster Analysis - Gong, Zhaoyang; Xu, Haocheng; Yang, Yong; Xia, Xinlei; Lyu, Feizhou; Jiang, Jianyuan; Wang, Hongli; Ma, Xiaosheng (Clinical spine surgery, 2024)
Cross-sectional study. To propose a novel cervical sagittal classification for asymptomatic people so as to deepen the understanding of cervical sagittal alignment. Cervical spine sagittal morphology varies in people. There is a lack of widely-accepted cervical sagittal classification method. In all, 183 asymptomatic subjects were included. A series of global and segmental cervical sagittal parameters were measured. Subjects with cervical lordosis (CL)<0 degrees were incorporated directly into the kyphosis (K) group. For subjects with CL ≥0 degrees, a two-step cluster analysis was used to arrive at the optimal number of clusters. The results of the expressions for the subtypes were derived by graphing. The 60 randomly selected lateral cervical spine films were evaluated by 4 spine surgeons at 4-week intervals using our classification method, the Toyama classification method and the Donk classification method. The 3 classification methods' reliability was expressed by the intra-group correlation coefficient (ICC), and convenience was expressed by the measuring time. Finally, the distribution of 4 subtypes was depicted, and sagittal parameters were compared among subtypes. Four subtypes of the cervical spine were suggested: Large lordosis (LL): CL≥-1.5×T1 slope (TS)+70°; Small lordosis (SL): -1.5×TS+50°≤CL<-1.5×TS+70°; Straight (S): 0°≤CL<-1.5×TS+50°; and K: CL<0°. The measuring time for our classification method was significantly less than the Toyama classification method ( P <0.001). Our classification method showed high inter-observer reliability (ICC=0.856) and high to excellent intra-observer reliability (ICC between 0.851 and 0.913). SL was the most common type (37.7%). Men had more LL type and women had more S type and K type. The proportion of S and K increased with age. Cervical sagittal parameters were significantly different among the subtypes except for C4 vertebral body (VB) angle ( P =0.546), C2-C7 SVA ( P =0.628) and NT ( P =0.816). We proposed a novel cervical sagittal classification for an asymptomatic population, which proved to be simple to implement with satisfactory reliability.